Block copolymer microparticles comprising inverse bicontinuous phases prepared via polymerization-induced self-assembly. Issue 15 (18th March 2019) - Yang, Pengcheng; Ning, Yin; Neal, Thomas J.; Jones, Elizabeth R.; Parker, Bryony R.; Armes, Steven P.
Abstract : Scalable preparation of micrometer-sized diblock copolymer particles exhibiting complex internal structure is achieved by RAFT-mediated polymerization-induced self-assembly (PISA). Abstract : Traditionally, post-polymerization processing routes have been used to obtain a wide range of block copolymer morphologies. However, this self-assembly approach is normally performed at rather low copolymer concentration, which precludes many potential applications. Herein, we report a facile method for the preparation of block copolymer particles exhibiting complex internal morphology via polymerization-induced self-assembly (PISA). More specifically, a series of diblock copolymers were synthesized by reversible addition–fragmentation chain transfer (RAFT) alternating copolymerization of styrene (St) with N -phenylmaleimide (NMI) using a poly( N, N -dimethylacrylamide) (PDMAC) stabilizer as a soluble precursor. Conducting such PISA syntheses in a 50 : 50 w/w ethanol/methyl ethyl ketone (MEK) mixture leads directly to the formation of micrometer-sized PDMAC-P(St- alt -NMI) diblock copolymer particles at 20% w/w solids. Adjusting the degree of polymerization (DP) of the core-forming P(St- alt -NMI) block to target highly asymmetric copolymer compositions provides convenient access to an inverse bicontinuous phase. TEM studies of intermediate structures provide useful insights regarding the mechanism of formation of this phase. SEM studies indicate that the final copolymer particles comprise perforated surface layers and possess nanostructured interiors. In addition, control experiments using 1, 4-dioxane suggest that the high chain mobility conferred by the MEK co-solvent is essential for the formation of such inverse bicontinuous structures. One-pot PISA formulations are reproducible and involve only cheap, commercially available starting materials, so they should be readily amenable to scale-up. This augurs well for the potential use of such nanostructured micrometer-sized particles as new organic opacifiers for paints and coatings.